COVID-19 and its effects on the driving style of spanish drivers - Corcoba, V?ctor (2022)
Spain is one of the countries most affected by COVID-19. Until May 5, 2021 there have been 3.54 million people infected and 78,399 deaths according to the Johns Hopkins Institute. This has meant that Spain is one of the countries in the world where the most restrictive measures have been adopted and which have had a strong impact on the economic, social, and mental health of citizens. One of the consequences of this pandemic is a severe increase in the strain on the healthcare system. Many of those infected had to be admitted to hospitals and even to Intensive Care Units (ICU). In this scenario, it is essential to reduce traffic accidents in order to avoid overcrowded hospitals. However, the Spanish General Directorate of Traffic highlights in several traffic reports that despite the decrease in the volume and distance of trips, the number of traffic accidents has not altered significantly and even during some periods has been higher than before the pandemic. The aim of this work is to establish if there has been a change in the driving style of drivers during the pandemic and to identify the group of people adopting a more inefficient and unsafe driving style. To this end, a study was carried out with 30 volunteers and their current driving style was compared with their driving style before the pandemic. The results show that drivers have adopted a more aggressive driving style than before the pandemic, especially women and those who have suffered anxiety due to COVID-19.